Water treatment plant sludge dewatering using geotextile bags: with and without lateral constraints - Urashima, Denise de Carvalho; Guimarães, Mag Geisielly Alves; Pereira, Marcus Vinicius Mendes (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – To evaluate the performance of geotextile (GTX) bags in terms of dewatering sludge derived from a Water Treatment Plant (WTP)—with and without lateral constraints (LCs)—through cyclic fillings.Methodology – The research was conducted through field tests. Sludge was collected from the decanters of a WTP, and this was followed by an evaluation of the chemical conditioning of this waste with cone tests. The sludge was subsequently dewatered in GTX bags under two experimental conditions, namely, with LCs and without LCs, both of which were performed in replicates. The tests included three successive filling cycles, with monitoring of the turbidity (NTU), filtrate mass (kg), mass retained in the bags (kg), filling height and total solid (TS) content in the sludge and filtrate (mg/L). Additionally, efficiency parameters, including the filtration efficiency (FE), the dewatering efficiency (DE), passing solid (SP) rate and piping (PP), were determined.Originality/relevance – The study addresses contemporary challenges related to the treatment and proper disposal of waste generated by WTPs. In the context of the dewatering of sludge under conditions with LCs and without LCs, the technical feasibility of the use of GTX systems in confined environments, GTX systems that are subjected to lateral forces, and the use of GTX systems in emergency situations is discussed. The aim is to broaden the application perspectives of this technology, as evidenced in the specialized literature.Results – Chemical conditioning is relevant to making the dewatering of solid wastes with high liquid contents and high levels of resistances to filtration viable. In this context, the anionic polymer A110 was used at a concentration of 0.2% and dosage of 30 mL/L. The tests performed with LCs showed better efficiency, with a FE of 99.5%, a SP rate of 0.5% and a particles loss (PP) of 0. 8 g/m². Additionally, lower turbidity values were recorded in the filtrates obtained under dewatering conditions with LCs.Theoretical/methodological contributions – The study contributes to the advancement of knowledge concerning WTP sludge dewatering processes implemented in GTX systems to provide technical support for decision-making tasks related to the chemical conditioning of sludge, evaluations of boundary conditions and the behavior of dewatering with LCs, which is based on efficiency parameters. Thus, the study provides elements that can guide the adoption and success of this technology in WTPs, especially in scenarios with limited areas available for treatment.Social and environmental contributions – This study highlights the emergency situation concerning the treatment and proper disposal of WTP sludge and the search for social and environmental sustainability. Dewatering technology involving GTX systems enables the proper management of these industrial wastes and their direct alignment with sustainable development goals (SDGs), especially SDGs 6, 9, 11, 12, 14 and 15.
Keywords: Social and environmental sustainability; Dewatering in geotextile bags; Sludge from Water Treatment Plants